2021
DOI: 10.28925/2312-5829.2021.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management as the Basis of Quality of Higher Education

Abstract: In this article, the use of the actualization of the problem of the knowledge management process, which is due to the need to mobilize scientific activity, practical implementation of scientific results and improve the quality of higher education. In the latest conditions of the pandemic crisis, there are significant changes in the organization of the culture of knowledge management and quality improvement in the modern system of higher education. The effectiveness of distance learning and distance organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The findings of the study showed that nurturing is the key to effective knowledge management and that effective knowledge management can facilitate collaboration in the higher education sector [6]. Horban used knowledge management to improve the management model of higher education institutions in order to enhance the quality of higher education, the results of the study showed that adding small additional projects can enhance the quality in higher education management [7]. Jarrahi et al carried out personal knowledge management and knowledge construction in response to the emphasis of personal knowledge management on individual knowledge workers acquiring knowledge in the organizational environment.…”
Section: Related Workmentioning
confidence: 99%
“…The findings of the study showed that nurturing is the key to effective knowledge management and that effective knowledge management can facilitate collaboration in the higher education sector [6]. Horban used knowledge management to improve the management model of higher education institutions in order to enhance the quality of higher education, the results of the study showed that adding small additional projects can enhance the quality in higher education management [7]. Jarrahi et al carried out personal knowledge management and knowledge construction in response to the emphasis of personal knowledge management on individual knowledge workers acquiring knowledge in the organizational environment.…”
Section: Related Workmentioning
confidence: 99%
“…The calculations of the city development strategy, carried out by the Omelchenko administration, were based on the theoretical basis of the traditional economy. At the same time, as modern research shows, historical heritage, creativity and cultural industries require specifi c methods of economic analysis, which are developed in the fi eld of cultural economics [9,10].…”
Section: O Horbanmentioning
confidence: 99%
“…The approach includes evaluating the current gap in the group’s knowledge needs and proposing an iterative strategy for bridging the gap. It aims at identifying higher education institutions’ strategic needs depending on organizational objectives, organizational hierarchical system, stakeholders, and procedures ( Horban, 2021 ). The next stage is to identify the knowledge fissure as well as the variables that contribute to it ( Nur et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…These publications look at how knowledge and information may be used as important organizational resources. Knowledge management (KM) plays dynamic role which is critical in higher education institutions (HEIs), notably in terms of planning, organizing, monitoring, and managing KM assets connected to intellectual capital ( de la Torre et al, 2021 ; Horban, 2021 ; Migdadi, 2021 ; Pereira et al, 2021 ; Terán-Bustamante et al, 2021 ). As a result, knowledge management might improve knowledge exchange and overall performance.…”
Section: Introductionmentioning
confidence: 99%